Application of an Existing Syndromic Surveillance System to Quantify Possible Cases of Opioid-associated Amnestic Syndrome in Massachusetts. Issue 6 (November 2022) - Barash, Jed A.; Ergas, Rosa; Parikh, Megha; Klevens, R. Monina; DeMaria, Alfred
Abstract : Objectives: In recent years, an opioid-associated amnestic syndrome (OAS) was identified in Massachusetts through elicited reporting by health care providers (traditional surveillance, TS). Whether OAS occurs more frequently and with a wider spatiotemporal distribution in Massachusetts remains unclear. We compared the frequency and spatiotemporal characteristics of emergency department (ED) visits for possible OAS (pOAS) using a pre-existing syndromic surveillance system (SyS) with OAS cases captured through TS. Methods: SyS was queried for Massachusetts ED visits in 15- to 55- year-olds with a chief complaint text and discharge codes for memory loss in association with codes for opioid use (pOAS). SyS data were extracted for 2016–2020, whereas TS was conducted for 2012–2018. Cases identified by SyS and TS were stratified by demographic and spatiotemporal variables. Results: TS ascertained 22 reported cases of OAS (18 males) between 2012 and 2018, ranging from 0 to 5 annually. No identified OAS patients presented between January and March or in western Massachusetts. Between 2016 and 2020, SyS identified 82 ED visits (49 males) with pOAS, ranging from 13 to 22 per year. Over the 5-year period, at least 2 ED visits for pOAS occurred during each month of the year (24 total during January, February, or March) and at least 1 visit occurred in each county except 2, with the second largest number (11) in Berkshire County (at the western border of Massachusetts), where no cases were ascertained through TS. Conclusions: Although OAS is a relatively rare condition, use of SyS in Massachusetts suggests a broader and more frequent spatiotemporal distribution than previously indicated from TS.